Occurrence and antibacterial resistance of culturable antibiotic-resistant bacteria in the Fildes Peninsula, Antarctica. (January 2021) - Na, Guangshui; Zhang, Wanli; Gao, Hui; Wang, Caixia; Li, Ruijing; Zhao, Fuqiang; Zhang, Keyu; Hou, Chao
Abstract: Quantifying the occurrence of Antarctic antibiotic-resistant bacteria (ARB) is essential for assessing the level of pollution and assessing the "baseline" or background level of ARB in human uninhabited environments. Animal feces, soil, and sediments were sampled from Fildes Peninsula. The abundance of sulfamethazine- and ciprofloxacin-resistance bacteria and antibotic resistance genes (ARGs) within ARB were investigated. The results showed Ciprofloxacin- and Sulfamethazine-resistant bacteria isolated from samples accounted for the highest abundances of 30 CFU/g and 79.8 CFU/g, respectively. The dominant genus of Sulfamethazine-and quinolone -resistance bacteria was Pseudomonas and Arthrobacter, respectively. 106 ARGs were detected from ARB. Strong positive correlations between mobile genetic elements (MGEs) and ARGs were found, what is relatively novel observation that the mechanism is confirmed to also occur in the Antarctic. This study reveals the compositional characteristics of ARGs of strains in Antarctic, providing support for the source of Antarctic antibiotic resistance and drug resistance mechanisms. Graphical abstract: Unlabelled Image Highlights: The occurrence of antibiotic-resistant bacteria (ARB) in the Fields Peninsula were investigated with sulfamethazine and ciprofloxacin, which is relatively low levels ARB pollution is affected by human activities. ARB in the Fildes Peninsula has become a repository of resistance genes via QPCR detection MGEs promoted horizontal transfer in Antarctic ARB, for example pikR2, sulA/folP-03, strB.